Research trends in the relationship between vitamin D and type 2 diabetes mellitus: a 20-year bibliometric and visualization analysis - Xu, Ruijun; Shao, Xuejing; Qiao, Huibo; Yan, Han; Xue, Yi (Frontiers in Endocrinology, 2024)
Vitamin D has a significant correlation with type 2 diabetes. Insufficient levels of vitamin D can cause insulin resistance, which impairs the ability of cells to respond to insulin and worsens the progression of diseases. Furthermore, vitamin D has the potential to enhance the release of insulin, enhance the regulation of blood sugar levels, and reduce the glycemic index. Research has indicated that insufficient levels of vitamin D may elevate the likelihood of experiencing complications related to type 2 diabetes, including cardiovascular disease and neuropathy. This study employed bibliometric analysis to investigate recent advancements in research about the relationship between vitamin D and type 2 diabetes. We searched for articles on the topic of vitamin D and type 2 diabetes published between January 1, 2004, and December 31, 2023. The search was performed on February 20, 2024, using the Web of Science Core Collection (WoSCC). Utilizing VOSviewer and CiteSpace, we conducted bibliometric analysis and visualization. A comprehensive study was conducted on a total of 1362 papers pertaining to the relationship between vitamin D and type 2 diabetes. The United States had the biggest number of publications and the highest effect among these articles. Within the top 10 most published journals, the journal "DIABETES CARE" has the highest H-index, indicating its significant influence in this field of study. Currently, there is an extensive body of research on the supplementation of vitamin D for the improvement of type 2 diabetes and prevention of complications in type 2 diabetes, as well as its related mechanisms. Research related to bone turnover and peripheral neuropathy represents a promising area for future studies. Overall, bibliometrics may assist researchers in comprehending the trajectory, significant themes, and scholarly influence of the field concerning vitamin D and type 2 diabetes. This, in turn, offers substantial backing for future studies that delve further into the subject matter.